Diurnal Thermal Regime in a Peat-Covered Palsa, Toolik Lake, Alaska - Nelson, F.E.; Outcalt, S.I.; Goodwin, C.W.; Hinkel, K.M. (ARCTIC, 1985)
Strong spatial and temporal variations in temperature and effective thermal diffusivity are apparent from short-term thermal records measured in the peat atop an ice-cored palsa in northern Alaska. Intersite differences in near-surface temperature regimes apparently result from topographic influences, vegetative cover, and site wetness. Values of effective thermal diffusivity indicate that ablation of the ice core is inhibited by advection of cold water near the ice-peat contact and by internal evaporation near the surface. These findings support the conclusions of earlier investigators, who emphasized the importance of peat for maintaining palsas near their equatorward limit.Key words: active layer, frost mound, palsa, peat, permafrost, soil temperature, thermal properties, Alaska Mots clés: couche active, tertre de gel, palsa, tourbe, pergélisol, température du sol, propriétés thermiques, Alaska